Efektivitas Buah Pepaya Terhadap Kelancaran Produksi Asi pada Ibu Postpartum : Studi Kasus - Hellen Febriyanti; Liswandari Liswandari; Meri Wiliandari (Universitas Harapan Bangsa Purwokerto, 2023)
The presentation coverage of exclusively breastfed babies in Indonesia is 67.74% and the presentation coverage of exclusively breastfed babies in Lampung province is 69.33%. One of the causes of the low coverage of exclusive breastfeeding for infants under the age of six months is due to milk production in postpartum mothers that are not smooth. One effort to increase breast milk production is to consume papaya fruit. The purpose of this study was to determine the effectiveness of papaya fruit on the smooth production of breast milk in postpartum mothers. This method of obstetric care is a case study of three postpartum mothers. The intervention given was papaya fruit for 14 consecutive days. The results of this obstetric care showed that there was an increase in breast milk production after consuming papaya fruit. It is expected that breastfeeding mothers should regularly consume papaya fruit, because giving papaya fruit (Carica Papaya L.) to nursing mothers can stimulate in increasing the secretion and amount of breast milk production (ASI).